The Double Stage of Working Mothers in Media Company - Aulia, Nurul; Gunawan, Wahyu; Yunita, Desi; Tajuddin, Nor Azlin (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2025)
The phenomenon of working mothers balancing dual roles as professionals and homemakers is a significant concern within the media industry context, including those working in online media, Kompas.com. This study aims to understand how working mothers in Kompas.com manage these two roles. The research uses a qualitative approach with a case study method. The data was collected through in-depth interviews with three informants from Megapolitan's editorial division. The results show that informants play a professional role at the “front stage” as self-disciplined, target-oriented, and communicative workers, while doubling as homemakers “backstage” who take care of children and the household. An analysis using Erving Goffman's dramaturgy theory shows that they balance these roles and identities by utilizing impression management. This study shows that working mothers in the media industry are active actors who develop social strategies to play their dual roles, highlighting the importance of support for women in both the workplace and the household.